An association analysis at 2q36 reveals a new candidate susceptibility gene for juvenile absence epilepsy and/or absence seizures associated with generalized tonic-clonic seizures - TÜRKDOĞAN, DİLŞAD; AĞAN YILDIRIM, KADRİYE (WILEY, 2011)
Purpose: To further evaluate the previously shown linkage of absence epilepsy (AE) to 2q36, both in human and WAG/Rij absence rat models, a 160-kb region at 2q36 containing eight genes with expressions in the brain was targeted in a case-control association study involving 205 Turkish patients with AE and 219 controls. Methods: Haplotype block and case-control association analysis was carried out using HAPLO VIEW 4.0 and inhibin alpha subunit (INHA) gene analysis by DNA sequencing. Key Findings: An association was found between the G allele of rs7588807 located in the INHA gene and juvenile absence epilepsy (JAE) syndrome and patients having generalized tonic-clonic seizures (GTCS) with p-values of 0.003 and 0.0002, respectively (uncorrected for multiple comparisons). DNA sequence analysis of the INHA gene in 110 JAE/GTCS patients revealed three point mutations with possible damaging effects on inhibin function in three patients and the presence of a common ACTC haplotype (H1) with a possible dominant protective role conferred by the T allele of rs7588807 with respective p-values of 0.0005 and 0.0014. Significance: The preceding findings suggest that INHA could be a novel candidate susceptibility gene involved in the pathogenesis of JAE or AE associated with GTCS.
Keywords: Absence epilepsy; Association study; Haplotype blocks; INHA gene; INHIBIN ALPHA-SUBUNIT; MUTATION; ACTIVIN; GABRB3; LOCI; LOCALIZATION